PENGARUH METODE LATIHAN SIRKUIT, METODE KONVENSIONAL DAN MOTIVASI BERPRESTASI TERHADAP KEMAMPUAN LOMPAT JAUH GAYA JONGKOK - Ahmad Yani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
Based on the researcher’s observation on the field, it seems that the ability of students of SMK Teknologi Riau in long jump is still low, and many students don’t have good enough techniques of long jump itself, besides that, the training method that is used is not appropriate yet. The purpose of this research is to find out the effect of circuit training method, conventional method and motivation performance towards the students’ long jump ability at SMK Teknologi Riau. This type of this research is quasi-experimental using factorial 2x2, the population of this research are the tenth grade students of SMK Teknologi Riau consist of 107 students, while the samples of this observation are 88 male students and make this sample become 27% high group (27% from 88 students=24 male students) and 27% low group (27% from 88 male students=24students), so that the total sample who are given the methods are 48 students. The instrument that is used is long jump test. The data has been analyzed by two ways anava and Tuckey test. The result of data analysis shows that: (1) There are different of result of long jump ability between circuit and conventional groups ( Fvalue = 4.75 ˃ Ftable = 4.06 ), (2) There are interaction between training method and motivation (Fvalue = 46.35 ˃ Ftable = 4.06 ), (3) The motivation got high category, the ability of students long jump who are given circuit method are better than the students who are given conventional method (Qh = 3.08 ˃ Qt = 2.91 ), (4) In the motivation has got low category, the ability of students’ long jump who are given conventional method is better than the students who are given circuit method ( Qh = 3.85 ˃ Qt= 3.76 ).